Sparking a change: Three years ago, Dzameer Dzulkifli founded Teach For Malaysia out of a desire to improve Malaysia's state of education and a passion for developing local talent. Today he faces the challenges of growing the organisation and addressing the criticism levelled against it. - The, Heat (The Heat, 2014)
WHETHER it is the flip-flopping of the medium of instruction in national schools or the debatable quality of teachers, the state of education in Malaysia is a hot button issue at every mealtime conversation.It was no different for colleagues Dzameer Dzulkifli and Keeran Sivarajah, who were discussing how to improve education in Malaysia during a mamak session in 2009.However, unlike others who merely air their dissatisfaction, they decided to act upon it.